2016
DOI: 10.2135/cropsci2015.02.0134
|View full text |Cite
|
Sign up to set email alerts
|

Variation Among Maize Hybrids in Response to High Vapor Pressure Deficit at High Temperatures

Abstract: Temperature and vapor pressure deficit (VPD) are two important environmental factors influencing stomatal conductance and transpiration. A limited transpiration rate (TRlim) trait expressed under high VPD has been shown to offer an approach to increase crop yield in water‐limited areas. The benefit of the TRlim trait is that it lowers the effective VPD under which plants lose water and so conserves soil water to support crop growth for use during drought periods later in the growing season. Previous studies at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 14 publications
2
51
0
Order By: Relevance
“…To ameliorate the impact of drought on crop yields, the critical need is commonly to improve crop performance in expectation of developing soil water deficits. The traits that appear to be particularly desirable to improve yield performance under water-deficit conditions generally are associated with limiting water use by the crop early in the growing season so that water is conserved for use later in season to sustain plant productivity during reproductive development [ 15 , 16 , 17 , 18 ]. To achieve soil water conservation early in the growing season there are two prime mechanisms for water conservation, both of which appear to be closely related to AQPs activity: (i) transpiration sensitivity to soil drying and (ii) transpiration sensitivity to high atmospheric vapor pressure deficit (VPD).…”
Section: Plant Water Usementioning
confidence: 99%
“…To ameliorate the impact of drought on crop yields, the critical need is commonly to improve crop performance in expectation of developing soil water deficits. The traits that appear to be particularly desirable to improve yield performance under water-deficit conditions generally are associated with limiting water use by the crop early in the growing season so that water is conserved for use later in season to sustain plant productivity during reproductive development [ 15 , 16 , 17 , 18 ]. To achieve soil water conservation early in the growing season there are two prime mechanisms for water conservation, both of which appear to be closely related to AQPs activity: (i) transpiration sensitivity to soil drying and (ii) transpiration sensitivity to high atmospheric vapor pressure deficit (VPD).…”
Section: Plant Water Usementioning
confidence: 99%
“…Future climate extremes are likely to strike crop growth as concurrent heat and drought events, thus setting higher demand for agricultural adaptations as the optimal breeding or management strategy may differ among stresses . A number of crop traits can be potentially adopted to ameliorate drought stress, including the limited-transpiration trait that can stabilize or even lower transpiration rates of both maize and soybean under high VPD conditions (Sinclair et al, 2010;Messina et al, 2015;Shekoofa et al, 2016). Yet limiting transpiration may bring the side effect of enhancing temperature stress, as canopy transpiration is a major pathway for latent heat flux.…”
Section: Spatial Variability In Climate Stressmentioning
confidence: 99%
“…Since these experiments were performed in growth chambers, it is likely that the high temperatures (> 35°C) that were required to reach higher VPD values played a role in the observed responses. It is difficult to clarify interactions between plant VPD responses and temperature from existing literature because these interactions are often confounded experimentally (Sermons et al, 2012;Shekoofa et al, 2016). However, recently, Shekoofa et al (2016) investigated the conservation of the BP in maize lines expressing the limited transpiration trait at 32°C under temperatures up to 38°C.…”
Section: Lentil Genotypes Transpiration Response To High Vpdmentioning
confidence: 99%
“…It is difficult to clarify interactions between plant VPD responses and temperature from existing literature because these interactions are often confounded experimentally (Sermons et al, 2012;Shekoofa et al, 2016). However, recently, Shekoofa et al (2016) investigated the conservation of the BP in maize lines expressing the limited transpiration trait at 32°C under temperatures up to 38°C. Interestingly, this study reported that some maize hybrids had lost the VPD breakpoints when temperature increased from 36 to 38°C.…”
Section: Lentil Genotypes Transpiration Response To High Vpdmentioning
confidence: 99%